(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
In the given article high-strength concrete are compositions selected and experimentally obtained. The concrete are defined physical and mechanical properties. The group of authors examines the use of high-strength concrete in concrete filled steel tube elements. Keywords: сoncrete filled steel tube, high-strength concrete, strength of concrete.